Zircon U-Pb ages and geochemistry of Early Cretaceous volcanic rocks, northwestern Korean Peninsula: Constraints on Late Early Cretaceous continental arc distribution in Northeast Asia - Yang, Jonghyok; Ku, Hyonchol; Pak, Ung; Ri, Chungil; Kim, Myongchol; Jong, Cholsu; Pak, Hyonuk; Kim, Jongnam; Ju, Songhyok; Kim, Cholhyon; Yun, Jusong; Kim, Sunghyon (Journal of Asian Earth Sciences: X, 2022)
•Early Cretaceous volcanic rocks are widespread in NW Korean Peninsula.•Magma sources of volcanic rocks were contaminated by crust materials or derived from enriched mantle.•The volcanic rocks were formed in continental arc setting associated with the Paleo-Pacific plate subduction. In the northwestern Korean Peninsula, Cretaceous volcanic rocks are composed of andesite, andesite-dacite and rhyolite intercalated with terrigenous clastic rocks. Zircon grains selected from these rocks are authigenic zircons with obvious crystal edges and oscillatory zoning, their Th/U ratios being generally larger than 0.4 (0.16–2.22), indicating magmatic origin. Most rocks were formed at Early Cretaceous Albian (113–103 Ma) and partially, at late Aptian, Prior to this time magmatism took place at 125 Ma and 135 Ma. All the negative εHf(t) values mean that these magma sources were contaminated by crust materials or derived from enriched mantle. Volcanic rocks belong to calc-alkaline series and partially to peraluminous series with relatively high alkali content. Chondrite-normalized REE patterns display right-lean LREE rich type and Primitive-mantle-normalized REE patterns do obvious negative anomalies in LILE (Ba, Sr), HFSE (Nb, Ta, P, Zr, Ti), but obvious positive anomalies in LIL (Rb, Pb) and HFS (Th, U, Nd). These volcanic rocks were formed in continental arc setting and their geochemical properties being similar to those of arc ADR (normal Island-Arc Andesite-Dacite-Rhyolite) suite rather than those of adakite. In the Late Early Cretaceous, west area of northeastern Asia including western Liaoning, China was in extensional setting but east area of northeastern Asia including northwestern Korean Peninsula, Jihei, eastern China and Far East areas, Russia were in continental arc setting.